Solar radiation and functional traits explain the decline of forest primary productivity along a tropical elevation gradient - Fyllas, Nikolaos M. (2017)
One of the major challenges in ecology is to understand how ecosystems respond to changes inenvironmental conditions, and how taxonomic and functional diversity mediate these changes. Inthis study, we use a trait-spectra and individual-based model, to analyse variation in forest primaryproductivity along a 3.3 km elevation gradient in the Amazon-Andes. The model accuratelypredicted the magnitude and trends in forest productivity with elevation, with solar radiation andplant functional traits (leaf dry mass per area, leaf nitrogen and phosphorus concentration, andwood density) collectively accounting for productivity variation. Remarkably, explicit representationof temperature variation with elevation was not required to achieve accurate predictions offorest productivity, as trait variation driven by species turnover appears to capture the effect oftemperature. Our semi-mechanistic model suggests that spatial variation in traits can potentiallybe used to estimate spatial variation in productivity at the landscape scale.